KMstability: R tools to report the stability and precision of Kaplan-Meier estimates as well as measures of follow-up in time-to-event studies - Erdmann, Stella; Betensky, Rebecca (SoftwareX, 2024)
In order to appropriately report time-to-event analyses by means of Kaplan-Meier estimates, its precision and stability should be described. The precision is often reported by confidence intervals. For reporting the stability, various measures of the follow-up time distribution are used. However, these do not provide the intended insight. Recently, a new stability measure was presented. We have developed the software KMstability for calculation and display of this stability measure, including a user-friendly R shiny application and an open-source R package. The software enables informative reporting of time-to-event analysis. This is essential for reporting time-to-event analyses at interim-analyses of clinical trials and for observational (real-world-data) studies.
Online verfügbar: 13. Februar 2024
Gesehen am 14.08.2024